1981
DOI: 10.1103/physrevlett.47.128
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Measurements of Solidn-H2andn-et al.

Abstract: Using a five-pass interferometric Brillouin spectrometer, we have measured the pressure dependence of longitudinal-and transverse-acoustic velocities and refractive index of solid n-H 2 andw-D 2 at room temperature in a diamond-anvil cell up to 200 kbar. The equations of state have been determined (55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…15͒ at pressures up to 4.5 GPa and 300 K. These results are compared with our previous results for H 2 shows only the molecular rotation ͑ϫ᭺͒. In the structure of ͑b͒ CH 4 , the directions of polarization for a LA and two TA modes propagating along ͗110͘ direction are shown to define the elastic anisotropy Aϭ( TA 2 / TA 1 ) 2 ϭ2C 44 /(C 11 ϪC 12 ).…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…15͒ at pressures up to 4.5 GPa and 300 K. These results are compared with our previous results for H 2 shows only the molecular rotation ͑ϫ᭺͒. In the structure of ͑b͒ CH 4 , the directions of polarization for a LA and two TA modes propagating along ͗110͘ direction are shown to define the elastic anisotropy Aϭ( TA 2 / TA 1 ) 2 ϭ2C 44 /(C 11 ϪC 12 ).…”
Section: Resultsmentioning
confidence: 50%
“…High-pressure Brillouin scattering can be used to probe acoustic velocities, which yield the determinations of elastic constants, bulk modulus, the refractive index, and the equation of state of materials. 2 Recently, we had developed high-pressure Brillouin spectroscopy for molecular single crystals grown in a DAC: 3,4 A complete mapping of the acoustic velocities in the various crystal directions, the refractive index, and the full set of adiabatic elastic constants can be exactly determined with in situ identification of the crystal orientation at each pressure by analyzing the observed angular dependence of acoustic velocities. This elaborate method has been applied to an important group of simple molecular solid phase encountered first at room temperature with increasing pressure: H 2 S, 3,5 CO 2 , 6 H 2 O, 7-9 CH 4 , 10 Kr, 11 and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These measurements are important for the calculation of high-pressure equations of state used in planetary modeling studies (2). Room-temperature Brillouin scattering spectra have been obtained for normal (para and ortho) fluid H2 and D2 pressurized to the freezing point at 5.4 GPa and for the solid phases from 5.4 to 20 GPa (25,26). These data yielded the pressure dependence of the longitudinal and transverse sound velocities, from which the bulk modulus as a function of pressure and the pressure-volume equation of state were calculated.…”
Section: Brillouin Scatteringmentioning
confidence: 99%
“…Measurements in fluid hydrogen at room temperature have produced the equation of state up to solidification (Shimizu 1981). Measurements on a single crystal up to 24 GPa have shown that solid hydrogen is elastically anisotrope (Zha 1993).…”
Section: 3j3j9*mentioning
confidence: 99%
“…In figure 9, the adiabatic sound velocities in liquid He (Polian 1986) and in liquid H 2 (Shimizu 1981) are plotted versus density at room temperature. A linear relation is observed above 0.13 g/cm 3 in liquid H 2 and above 0.45 g/cm 3 in liquid He.…”
Section: T(k)mentioning
confidence: 99%